Dinamika Motivasi Intrinsik dan Ekstrinsik Santri dalam Menghafal Kosakata Bahasa Arab (Mufradat): Studi Kasus di Pondok Pesantren Bustanul Ulum Mlokorejo Jember - Nuril Anwar (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2025)
This study aims to analyse the dynamics of intrinsic and extrinsic motivation among students in memorising Arabic vocabulary (mufradat) at the Bustanul Ulum Islamic Boarding School in Mlokorejo, Jember. The research problem focusses on the complex interaction between these two types of motivation within the unique context of pesantren education. The research method used is qualitative with a case study approach, where data was collected through in-depth interviews, participant observation, and document analysis, and then analysed thematically. The research findings reveal that santri motivation undergoes a dynamic transformation, forming a